2014
DOI: 10.1136/bmjopen-2013-004318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and resource utilisation in Medicare patients with chronic liver disease: a historical cohort study

Abstract: ObjectiveThe aim of this study is to assess recent trends in health resource utilisation and patient outcomes of Medicare beneficiaries with chronic liver disease (CLD).SettingLiver-related mortality is the 10th leading cause of death in the USA, and hepatitis C virus (HCV) and obesity-related non-alcoholic fatty liver disease are the major causes of CLD. As the US population ages and becomes more obese, the impact of CLD is expected to become more prominent for the Medicare population.ParticipantsThis is a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…There is a remarkable paucity of data addressing economic issues in patients with NAFLD [16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Our search identified six articles related to the economics of NAFLD (four for the general population, one in the C65 years old or medically disabled population) (Table 1) [20,23,[30][31][32][33].…”
Section: Publications Related To Economic Issues In Patients With Nonmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a remarkable paucity of data addressing economic issues in patients with NAFLD [16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Our search identified six articles related to the economics of NAFLD (four for the general population, one in the C65 years old or medically disabled population) (Table 1) [20,23,[30][31][32][33].…”
Section: Publications Related To Economic Issues In Patients With Nonmentioning
confidence: 99%
“…Predictors of cost common for both inpatients and outpatients were younger age and number of procedures. Although non-alcoholic cirrhosis includes a number of diagnostic categories, some of these patients may have had NAFLD [32].…”
Section: Publications Related To Economic Issues In Patients With Nonmentioning
confidence: 99%
See 1 more Smart Citation
“…analyzed claims associated with patients with chronic hepatitis C virus (HCV) and found increased risk of higher healthcare costs among patients with ≥2 comorbidities related to HCV (odds ratio: 2.78; 95% CI: 2.48–3.12) or unrelated to HCV (odds ratio: 2.19; 95% CI: 1.76–2.72). A study by Younossi et al . of Medicare beneficiaries with chronic liver disease reported that the number of diagnoses per claim were independent predictors of spending for hospitalization (3.7% payment increase; 95% CI: 3.1–4.3%) and outpatient care (25.5% payment increase; 95% CI: 25.1–25.8%).…”
Section: Introductionmentioning
confidence: 99%
“…10 A recent retrospective survey in United States of America (USA) found that chronic liver disease is associated with a significant increase in medical costs and healthcare resource utilization over time. 11 Pharmacotherapy for cholestasis includes symptomatic treatment of pruritus along with management of complications such as osteopenia and fatsoluble vitamin deficiencies. 1 …”
Section: Introductionmentioning
confidence: 99%